An analysis of curriculum knowledge in an introductory actuarial science course - Enderstein, Belinda (School of Education, 2016)
Actuarial Science is a sought after profession in South Africa with high attrition rates at university. The profession is small and dominated by white males. Slow transformation of the profession to reflect a more representative sample of the population is exacerbated by the long route to qualification. This study is an analysis of the first module of the redesigned course reader for the course 'Introduction to Actuarial Science' at the University Cape Town. It was prompted by the change in student engagement with and sentiment about the course in 2013. Data is concurrently analysed from two interviews with the course convenor exploring (a) the nature and description of the profession as well as what knowledge is valued in the field of practice and the discipline and (b) the reasons for the redesign of the course reader and the process itself. The first module of the course reader is analysed in tandem with the second interview data. The research aims to reveal the complexity of the knowledge of actuarial science which makes mastery of its content, methods and ways of thinking (summed up in the term epistemic access ) challenging. Thus careful curriculum design is important in orientating first year students to the discipline and profession. Educational theorists from the school of social realism provide conceptual frameworks through which one can identify knowledge structures and elements thereof in data. Basil Bernstein's Pedagogic Device is used in locating the course reader data in the field of recontextualisation, relying on recontextualising rules which 'regulate the formation of specific pedagogic discourse' (Bernstein, 2000, p.28) to examine the ways in which access to the discipline is facilitated in the course reader. In addition, Bernstein's pedagogic codes analysed by means of his concepts classification and framing are employed to analyse (a) the nature and description of the profession and (b) the knowledge valued in the discipline and in the field of practice. Karl Maton's Legitimation Code Theory and in particular the identification of specialisation codes on the basis of epistemic and social relation s affords the potential of understanding the key principles by which this knowledge form is legitimated. The writings of Young (2008) and Muller (2009 and Young and Muller (201 4 ) assist in delineating a few crucial issues on professional knowledge and the curriculum. This project seeks to analyse the curriculum knowledge and the pedagogic codes employed in the course reader of a newly designed introductory course to ascertain the nature of actuarial science and to suggest what forms of pedagogy might enable students to access that knowledge. Regarding the nature of actuarial science, the study found that it is a complex region that combines highly specialized techno-theoretical knowledge with specific forms of inferential reasoning and professional judgment required to address knotty problems in the business world. Regarding an effective pedagogy, the analysis of the course reader provides clues as to what an explicit, visible pedagogic discourse capable of providing access to this complex field to first generation students might entail.